Adsorption behavior comparison of trivalent and hexavalent chromium on biochar derived from municipal sludge. (August 2015) - Chen, Tan; Zhou, Zeyu; Xu, Sai; Wang, Hongtao; Lu, Wenjing
Highlights: The adsorption effect of Cr(III) on biochar is stronger than that of Cr(VI). Surface functional groups contribute weakly to adsorption. The main mechanism of adsorption involves surface precipitation and ion-exchange. Reduction operation is helpful to improve chromium removal. Abstract: In this work, static equilibrium experiments were conducted to distinguish the adsorption performance between the two valence states of chromium on biochar derived from municipal sludge. The removal capacity of Cr(VI) is lower than 7 mg/g at the initial chromium concentration range of 50–200 mg/L, whereas that of Cr(III) higher than 20 mg/g. It indicates that Cr(III) is much easier to be stabilized than Cr(VI). No significant changes in the biochar surface functional groups are observed before and after the adsorption equilibrium, demonstrating the poor contribution of organic matter in chromium adsorption. The main mechanism of heavy metal adsorption by biochar involves (1) surface precipitation through pH increase caused by biochar buffer ability, and (2) exchange between cations in solution (Cd 2+ ) and in biochar matrix (e.g. Ca 2+ and Mg 2+ ). The reduction of Cr(VI) to Cr(III) is necessary to improve removal efficiency of chromium.